TRANSFORMASI BUDAYA RUWATAN - Bambang Soelistyanto (Berkala Arkeologi, 1996)
This paper intends to discuss changes in the values of Ruwatan in a dynamic cultural context. The main idea that will be put forward in this text is about the change in the meaning of ruwatan which has shifted along with the development of society in identifying culture. This is based on philological and archaeological data which show that ruwat, which means destroying, destroying, or liberating has existed in the concept of Javanese beliefs since the 9th century AD.